REVITALISASI DAN REKONTRUKSI PEMIKIRAN PENDIDIKAN AGAMA ISLAM DALAM MENGHADAPI TANTANGAN DUNIA PENDIDIKAN MODERN - Iskandar Mirza; Akhmad Roziqin; Lia Amalia (Jurnal Pendidikan Nusantara, 2026)
This article examines the revitalization and reconstruction of Islamic Religious Education (IRE) thought in response to the challenges of modern education characterized by rapid advancements in science, technology, globalization, and social transformation. The study aims to analyze the urgency of renewing the paradigm of Islamic Religious Education to ensure its relevance, contextuality, and ability to meet the needs of learners in the modern era while maintaining the fundamental values of Islam. This research employs a library research method with a descriptive-analytical approach by reviewing various scholarly works related to Islamic educational thought and contemporary educational developments. The findings indicate that the revitalization of Islamic Religious Education should be carried out through the integration of religious and modern scientific knowledge, the implementation of student-centered learning approaches, the utilization of educational technology, and the cultivation of values such as moderation, critical thinking, creativity, and strong moral character. Furthermore, the reconstruction of Islamic educational thought requires a shift from a predominantly normative and doctrinal paradigm toward a more transformative, humanistic, and contextual approach. Therefore, Islamic Religious Education should not merely function as a medium for transmitting religious knowledge but also as an instrument for developing individuals who are faithful, morally responsible, adaptive, and competitive in the face of global societal dynamics. This study concludes that the revitalization and reconstruction of Islamic Religious Education thought are strategic efforts to enhance the quality of Islamic education while ensuring its relevance to contemporary challenges and its adherence to the values of the Qur’an and Sunnah.